Hubungan supervisi kepala ruang dengan implementasi sasaran keselamatan pasien di ruang rawat inap - Salsabila, Aninda Putri; Kurniasih, Yuni; Rokhmah, Noor Ariyani (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Patient safety has been a major concern in the healthcare world for the past two decades. Patient falls in Indonesia are reported as one of the three most common hospital incidents. The Special Region of Yogyakarta ranks third in the country for the number of incidents. If this situation is not addressed, the number of patient safety incidents will increase, service quality will decline, and public trust in hospitals will decline. Purpose: To determine the relationship between ward head supervision and the implementation of patient safety goals in inpatient wards. Method: This study used a quantitative cross-sectional design with a correlational approach. A sample of 60 nurses was selected through purposive sampling. Data were collected using a questionnaire regarding ward head supervision and the implementation of patient safety goals. The relationship was analyzed using Kendall's tau correlation test. Results: The majority of respondents (51.7%) reported adequate supervision of ward heads, and 48.3% reported good supervision of ward heads. Implementation of patient safety goals was categorized as good (100%). There is a significant relationship between ward head supervision and the implementation of patient safety goals (p-value = 0.001 <0.05) with a correlation coefficient of 0.320, indicating a positive relationship with low-moderate strength. Conclusion: There is a significant relationship between ward head supervision and the implementation of patient safety goals in inpatient wards.   Keywords: Head Nurse Supervision; Nurses; Patient Safety.   Pendahuluan: Keselamatan pasien telah menjadi perhatian utama di dunia kesehatan selama dua dekade terakhir. kejadian pasien jatuh di Indonesia dilaporkan sebagai salah satu dari tiga insiden terbesar yang terjadi di rumah sakit. Provinsi Daerah Istimewa Yogyakarta menempati urutan ketiga dalam jumlah kasus insiden di seluruh Indonesia. Apabila kondisi ini tidak ditangani, maka angka terjadinya insiden keselamatan pasien semakin tinggi, menurunnya mutu pelayanan, dan menurunnya kepercayaan masyarakat terhadap rumah sakit. Tujuan: Untuk mengetahui hubungan antara supervisi kepala ruang dengan implementasi sasaran keselamatan pasien di ruang rawat inap. Metode: Penelitian ini menggunakan desain kuantitatif cross-sectional dengan pendekatan korelasional. Sampel berjumlah 60 perawat yang dipilih melalui purposive sampling. Data dikumpulkan menggunakan kuesioner supervisi kepala ruang dan implementasi sasaran keselamatan pasien. Analisis hubungan menggunakan uji korelasi kendall’s tau. Hasil: Mayoritas supervisi kepala ruang cukup sebanyak (51.7%) responden dan supervisi kepala ruang baik sebanyak (48.3%) responden. Implementasi sasaran keselamatan pasien dalam kategori baik (100%). Terdapat hubungan signifikan antara supervisi kepala ruang dengan implementasi sasaran keselamatan pasien (p-value = 0.001<0.05) dengan koefisien korelasi 0.320 yang menunjukkan hubungan positif dengan kekuatan rendah-sedang. Simpulan: Terdapat hubungan yang signifikan antara supervisi kepala ruang dengan implementasi sasaran keselamatan pasien di ruang rawat inap.   Kata Kunci: Keselamatan Pasien; Perawat; Supervisi Kepala Ruang.